Genetically predicted sex hormone binding globulin and ischemic heart disease in men and women: a univariable and multivariable Mendelian randomization study - Jie V. Zhao (Nature Portfolio, 2021)
Abstract Men are more vulnerable to ischemic heart disease (IHD) than women, possibly due to testosterone. Correspondingly, sex hormone binding globulin (SHBG) which lowers circulating testosterone might protect men against IHD. SHBG may also affect IHD independent of testosterone, which has not previously been examined. To assess the sex-specific role of SHBG in IHD, in univariable Mendelian randomization (MR), we used sex-specific, genome-wide significant genetic variants to predict SHBG, and examined their association with IHD in the UK Biobank. We also replicated using genetic instruments from Japanese men and applied to Biobank Japan. To assess the role of SHGB independent of testosterone in men, we used multivariable MR controlling for testosterone. Genetically predicted SHBG was associated with lower IHD risk in men [odds ratio (OR) 0.78 per standard deviation, 95% confidence interval (CI) 0.70 to 0.87], and the association was less clear in women. The estimates were similar in Japanese. The inverse association remained after controlling for testosterone in men (OR 0.79, 95% CI 0.71 to 0.88). SHBG might lower the risk of IHD in men, with a role independent of testosterone. Exploring intervention strategies that increase SHBG is important for targeting IHD treatments.